Reverse engineering of B-pillar with 3D optical scanning for manufacturing of non-uniform thickness part - Islam, Md. Tasbirul; Abdullah, A.B.; Mahmud, Mohamad Zihad (EDP Sciences, 2016)
This paper presents reverse engineering (RE) of a complex automobile structural part, B-pillar. As a major part of the automobile body-in white (BiW), B-pillar has substantial opportunity for weight reduction by introducing variable thickness across its sections. To leverage such potential, an existing B-pillar was reverse engineered with a 3D optical scanner and computer aided design (CAD) application. First, digital data (i.e. in meshes) of exiting B-pillar was obtained by the scanner, and subsequently, this information was utilized in developing a complete 3D CAD model. CATIA V5 was used in the modeling where some of the essential work benches were ‘’Digitized Shape Editor’’, ‘’Quick Surface Reconstruction’’, ‘’Wireframe and Surface Design’’, ‘’Freestyle’’, ‘’Generation Shape Design’’ and “Part design”. In the final CAD design, five different thicknesses were incorporated successfully in order to get a B-pillar with non-uniform sections. This research opened opportunities for thickness optimization and mold tooling design in real time manufacturing.